Formation of Singularities for Quasilinear Hyperbolic Systems with Characteristics with Constant Multiplicity (Journal of Partial Differential Equations, 2003)
" In this paper we consider the Cauchy problem for quasilinear hyperbolic systems with characteristics with constant multiplicity. Without restriction on characteristics with constant multiplicity(> 1), under the assumptions that there is a genuinely nonlinear simple characteristic and the initial data possess certain decaying properties, the blow-up result is obtained for the C\u00b9 solution to the Cauchy problem."
Keywords: quasilinear hyperbolic system; Cauchy problem; formation of singularity; life-span